Perturbations in the upper layers of α Centauri A. Issue 1 (January 2016) - Brito, A; Lopes, I
Abstract: The emerging field of asteroseismology allows the direct study of stellar interiors with an incredibly high precision. We used a seismic parameter based on the phase shift as a diagnostic tool to infer the presence of a new layer of rapid variation in the external layers of the primary component of the stellar system Alpha Centauri AB. This layer is, apparently, a thin region where the acoustic modes suffer a strong scattering. Our tests indicate that this layer should be located at an acoustical depth of approximately 1400 s (0.939 R), which corresponds to a depth of 6% below the surface of the star. This is somehow unexpected since the internal structure of this sun-like star is predicted to be similar to the Sun.